Teknologi Microbubble untuk Meningkatkan Pertumbuhan Ikan Lele (Clarias sp.) - Bagus Dwi Hari Setyono; Lalu Wirahadi Al Baihaqi; Muhammad Marzuki; Lalu Mukhtar Atmawinata; Syawalina Fitria; Rangga Idris Affandi (Postgraduate, University of Mataram, 2023)
Catfish (Clarias sp.) is one of the economically important freshwater fish that has been widely cultivated both traditionally and intensively. Catfish has many advantages such as fast growth, resistance to disease, and can live in water conditions that are low in oxygen content. The use of microbubble technology is expected to support the performance of catfish farming with a biofloc system. With the application of this technology, it is hoped that the oxygen supply from micro-sized air bubbles will increase. Because the diameter of the air bubble is less than 50 Âµm, it is expected to last a long time in the water and can spread horizontally so that it can be utilized optimally by catfish and biofloc. The purpose of this study was to evaluate the effectiveness of microbubble technology on the growth performance of catfish. The research method used a completely randomized design, with 4 treatments and 3 replications. The variables measured during the study included survival rate, length and weight growth, specific growth rate, feed conversion ratio (FCR), and water quality including temperature, dissolved oxygen (DO), pH, ammonia (NH3), nitrite (NO2-), nitrate (NO3-), oxygen consumption rate (OCR), and total organic matter (TOM).